2020
DOI: 10.1002/aoc.5977
|View full text |Cite
|
Sign up to set email alerts
|

A 2D cadmium metal–organic framework: Synthesis, structure and luminescence sensing for chromate, permanganate, cupric, silver and ferric

Abstract: A multi‐responsive Cd metal–organic framework {[Cd (ttpe)(H2O)(ip)]•4H2O•DMAC}n (1•4H2O•DMAC) was synthesized using hydrothermal method (ttpe = 1,1,2,2‐tetra(4‐(1H‐1,2,4‐triazol‐1‐yl)phenyl)ethylene, ip = isophthalate, DMAC = N,N‐dimethylacetamide), and characterized. 1 exhibits a 2D (4,4) network. The luminescent sensing experimrnts showed that 1•4H2O•DMAC as a new MOF luminescent sensor can detect Cr2O72−, CrO42−, MnO4−, Cu2+, Ag+ and Fe3+ in aqueous solution with simultaneously high efficiency and high sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The relative standard deviation of the fluorescence intensity of the blank sample tested ten times for LMOF-1 was 0.051. The calculated detection limit of the Ag + ions is 0.9 × 10 −5 M. To the best of our knowledge, the K sv value of detecting Ag + is better than or comparable to those in the literature reported in the past, such as 44 and 45 It has been reported that the Ag + induced fluorescence decrease may be probably attributed to the ligand-to-metal charge transfer (LMCT). 44 At the same time, Fe 3+ also has a quenching effect on the emission of LMOF-1 in aqueous solution.…”
Section: Sensing Of Metal Ionssupporting
confidence: 69%
See 1 more Smart Citation
“…The relative standard deviation of the fluorescence intensity of the blank sample tested ten times for LMOF-1 was 0.051. The calculated detection limit of the Ag + ions is 0.9 × 10 −5 M. To the best of our knowledge, the K sv value of detecting Ag + is better than or comparable to those in the literature reported in the past, such as 44 and 45 It has been reported that the Ag + induced fluorescence decrease may be probably attributed to the ligand-to-metal charge transfer (LMCT). 44 At the same time, Fe 3+ also has a quenching effect on the emission of LMOF-1 in aqueous solution.…”
Section: Sensing Of Metal Ionssupporting
confidence: 69%
“…The calculated detection limit of the Ag + ions is 0.9 × 10 −5 M. To the best of our knowledge, the K sv value of detecting Ag + is better than or comparable to those in the literature reported in the past, such as {[Zn 5 (L) 2 (DMF) 2 (μ 3 -H 2 O)]·2DMF} (2.24 × 10 3 M −1 ), 43 {[Zn 6 Cl 6 (2,2′-dbpt) 3 ]·2H 2 O} n (1.67 × 10 4 M −1 ), 44 and {[Cd(ttpe)(H 2 O)(ip)]·4H 2 O·DMAC} n (1·4H 2 O·DMAC) (1.563 × 10 4 M −1 ). 45 It has been reported that the Ag + induced fluorescence decrease may be probably attributed to the ligand-to-metal charge transfer (LMCT). 44…”
Section: Resultsmentioning
confidence: 99%
“…They irreversibly damage the nervous system, DNA, and circulatory system, giving rise to various incurable diseases, such as organ failure, angiocardiopathy, malformation, and cancer. [6][7][8][9][10][11][12] For instance, chlortetracycline (Chl), an abused broad-spectrum antibiotic, is often widely used in the treatment and therapy of humans and as a feed additive in animal growth, which may cause serious side effects. 13,14 Redundant Ag(I) ions in an aqueous medium can damage the skin, eyes and even cause stomachache, epilepsy, kidney failure, and argyria.…”
Section: Introductionmentioning
confidence: 99%
“…A weak bond was formed between the oxygen atom and Fe 3+ or Cu 2+ , resulting in a change in the electronic energy level of the ligands and low energy transfer efficiency. [189][190][191][192][193][194] The K sv values were 5.2 × 10 4 L mol −1 for Cu 2+ and 4.3 × 10 4 L mol −1 for Fe 3+ . A pyrenefunctionalized MOF, MIL-53-L, has been synthesized to act as an efficient and selective luminescent chemical sensor for detecting Cu 2+ (Fig.…”
Section: Luminescence Sensing Towards Cu 2+mentioning
confidence: 99%